Inhibition of O-GlcNAcylation Decreases the Cytotoxic Function of Natural Killer Cells - Feinberg, Daniel; Ramakrishnan, Parameswaran; Wong, Derek P.; Asthana, Abhishek; Parameswaran, Reshmi (Frontiers in Immunology, 2022)
Natural killer (NK) cells mediate killing of malignant and virus-infected cells, a property that is explored as a cell therapy approach in the clinic. Various cell intrinsic and extrinsic factors affect NK cell cytotoxic function and an improved understanding of the mechanism regulating NK cell function is necessary to accomplish better success with NK cell therapeutics. Here, we explored the role of O-GlcNAcylation, a previously unexplored molecular mechanism regulating NK cell function. O-GlcNAcylation is a post-translational modification mediated by O-GlcNAc transferase (OGT) that adds the monosaccharaide N-acetylglucosamine to serine and threonine residues on intracellular proteins, and O-GlcNAcase (OGA) that removes the sugar. We found that stimulation of NK cells with the cytokines Interleukin-2 (IL-2) and Interleukin-15 (IL-15) results in enhanced O-GlcNAcylation of several cellular proteins. Chemical inhibition of O-GlcNAcylation using OSMI-1 was associated with a decreased expression of NK cell receptors (NKG2D, NKG2A, NKp44), cytokines (TNF-, IFN-), granulysin, soluble Fas ligand, perforin and granzyme B in NK cells. Importantly, inhibition of O-GlcNAcylation inhibited NK cell cytotoxicity against cancer cells. However, increases in O-GlcNAcylation following OGA inhibition using an OGA inhibitor or shRNA-mediated suppression did not alter NK cell cytotoxicity. Finally, we found that NK cells pretreated with OSMI-1 to inhibit O-GlcNAcylation showed compromised cytotoxic activity against tumor cells in vivo in a lymphoma xenograft mouse model. Overall, this study provides the seminal insight into the role of O-GlcNAcylation in regulating NK cell cytotoxic function.